2009
DOI: 10.1016/j.ajhg.2009.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal-Dominant Retinitis Pigmentosa Caused by a Mutation in SNRNP200, a Gene Required for Unwinding of U4/U6 snRNAs

Abstract: Mutations in genes associated with the U4/U6-U5 small nuclear ribonucleoprotein (snRNP) complex of the spliceosome are implicated in autosomal-dominant retinitis pigmentosa (adRP), a group of progressive retinal degenerative disorders leading to visual impairment, loss of visual field, and even blindness. We recently assigned a locus (RP33) for adRP to 2cen-q12.1, a region that harbors the SNRNP200 gene encoding hBrr2, another U4/U6-U5 snRNP component that is required for unwinding of U4/U6 snRNAs during splic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
153
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(157 citation statements)
references
References 52 publications
4
153
0
Order By: Relevance
“…In contrast, another non-synonymous variant p.A1995T, which occurred in both patients and controls, was predicted to be benign, suggesting it is unlikely to be pathogenic. Notably, the three DCMs p.Q885E, p.S1087L, and p.R1090L, which were previously identified in three respective adRP pedigrees from northern China, 21,22,33 were not found in our study. In the first sec-63 domain region, which harbors two of these three mutations (p.S1087L and p.R1090L), only three common SNPs (p.L1184L, p.S1218S, and p.S1230s) and three intronic changes (c.3365 Ăž 145 G4A, c.3366-25 A4G, and c.3639 Ăž 53_c.3639 Ăž 93del) were detected in our study subjects.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…In contrast, another non-synonymous variant p.A1995T, which occurred in both patients and controls, was predicted to be benign, suggesting it is unlikely to be pathogenic. Notably, the three DCMs p.Q885E, p.S1087L, and p.R1090L, which were previously identified in three respective adRP pedigrees from northern China, 21,22,33 were not found in our study. In the first sec-63 domain region, which harbors two of these three mutations (p.S1087L and p.R1090L), only three common SNPs (p.L1184L, p.S1218S, and p.S1230s) and three intronic changes (c.3365 Ăž 145 G4A, c.3366-25 A4G, and c.3639 Ăž 53_c.3639 Ăž 93del) were detected in our study subjects.…”
Section: Discussionmentioning
confidence: 41%
“…The RP33 locus, initially mapped to chromosomal region 2cen-q12.1, was identified in a large Chinese family with adRP. 20 Subsequent studies had identified two mutations, p.S1087L 21 and p.R1090L, 22 in the small nuclear ribonucleoprotein 200 kDa (U5) (SNRNP200, MIM 601664) gene to be segregated with RP in two respective large Chinese adRP families. SNRNP200 is a member of the RNA intron-splicing factor protein family and is widely expressed in human tissues.…”
Section: Introductionmentioning
confidence: 99%
“…2C). Consistent with the HB ratchet helix being involved in RNA unwinding, some brr2 mutations linked to the RP33 form of autosomal dominant retinitis pigmentosa in humans [60][61][62] lead to exchanges of RNA-contacting residues in this element (S1087L, R1090L). The S1087L RP33 exchange in human Brr2 reduces RNA affinity as well as ATPase and helicase activities 51 and RP33-like N1104L and R1107L exchanges in yeast Brr2 are associated with reduced ATPdependent U4/U6 unwinding in tri-snRNP preparations.…”
Section: Multiple Layers Of Helicase-associated Domains In Brr2mentioning
confidence: 94%
“…The S1087L RP33 exchange in human Brr2 reduces RNA affinity as well as ATPase and helicase activities 51 and RP33-like N1104L and R1107L exchanges in yeast Brr2 are associated with reduced ATPdependent U4/U6 unwinding in tri-snRNP preparations. 60 Mutation of a Brr2 element equivalent to the Hel308 separator loop resulted in reduction or loss of cell viability, 41,52 in line with a similar duplex disruption mechanism as in Hel308. However, in a yeast U4/U6 U5 tri-snRNP structure, 12 Brr2 is loaded on the U4/U6 di-snRNA with the putative separator loop distant from the U4/U6 duplex portion to be unwound and instead with an edge of the RecA2 domain abutting the end of this duplex region (Fig.…”
Section: Multiple Layers Of Helicase-associated Domains In Brr2mentioning
confidence: 96%
“…The disease onset and progression may vary significantly among patients, even within the same family. The patients frequently experience night blindness in the early phase of the disease, The molecular basis of human retinal and vitreoretinal diseases Collin et al, 2008; den Hollander et al, 1999; Dryja et al, 1995; Gal et al., 2000; Huang et al, 1995; Martinez-Mir et al, 1998;Maw et al, 1997;Maw et al, 2000;McLaughlin et al, 1993; Morimura et al, 1998;Nakazawa et al, 1998; Rivolta et al, 2000;Thompson et al, 2001;Tuson et al, 2004;Zangerl et al, 2006;Zhang et al, 2007b) or dominant (Abid et al, 2006; Bowne et al, 2002; Chakarova et al, 2002; Chakarova et al, 2007;Farrar et al, 1991;Freund et al, 1997;Friedman et al, 2009; Kajiwara et al, 1991; Kajiwara et al, 1994; Keen et al, 2002; Kennan et al, 2002;McKie et al, 2001; Rebello et al, 2004; Sato et al, 2005;Vithana et al, 2001;Wada et al, 2001;Zhang et al, 2007a;Zhao et al, 2009), as well as X-linked (Meindl et al, 1996; Roepman et al, 1996a; Roepman et al, 1996b; Schwahn et al, 1998).Interestingly, mutations in several genes can be either dominant or recessive (Bernal et al, 2008; Bessant et al, 1999; Coppieters et al, 2007;Davidson et al, 2009; Dryja et al, 1990; Morimura et al, 1999; Pierce et al, 1999;Sullivan et al, 1999). The splicing category will now be discussed in more detail.…”
mentioning
confidence: 99%